Echocardiographic predictors of ischemic mitral insufficiency recurrence after mitral annuloplasty - N.D. Oryshchyn; Yu.A. Ivaniv (Кардіохірургія та інтервенційна кардіологія)
The aim – to establish echocardiographic predictors of ischemic mitral insufficiency recurrence after surgical reduction annuloplasty of mitral valve (MV). Materials and methods. We assessed echocardiographic parameters of left ventricular remodeling and mitral valve deformation in 52 patients with ischemic mitral insufficiency and planned MV annuloplasty. Follow-up assessment with MV function evaluation was performed 6-12 months after surgery, recurrent mitral insufficiency was revealed in 11 patients. Patients with MR recurrence comprised group 1, without mitral insufficiency recurrence – group 2. Results. The groups did not differ with respect to demographic, clinical parameters and coronary artery stenoses. Indexes of left ventricle (LV) global and local remodeling and MV deformation differed significantly in two groups. We established cut-off values for each parameter of LV remodeling and MV deformation indicating increased frequency of mitral insufficiency after surgery. Coaptation height of over 10 mm and tenting area over 3.2 cm had high sensitivity (81.82 % and 100.00 % respectively) and specificity (82.93 % and 82.93 % respectively) in predicting mitral insufficiency recurrence, as well as end-systolic volume more than 110 ml (sensitivity 90.91 %, specificity 82.93 %). The multivariant model of independent prognostic factors of ischemic MR recurrence included 6 parameters (MV tenting area, MV coaptation height, LV end-diastolic and end-systolic volumes, interpapillary distance and posterior displacement of posterior papillary muscle). This model allows predicting MR after surgery with 94 % accuracy. Conclusion. Detailed echocardiographic analysis of remodeling parameters might help to identify patients with increased risk of mitral insufficiency recurrence after annuloplasty and suggest necessity to perform additional surgical procedures on ventricle or subvalvular apparatus.